Analisis Pemecahan Masalah Matematika Mahasiswa berdasarkan Taksonomi SOLO - Asep Rosadi; Nining Puji Lestari; Riska Yulianti; Luluk Wahyu Nengsih (Departement of Mathematics Education, 2022)
One of the abilities that must be possessed and mastered by a student in the 21st century is problem solving ability. Mathematical skills are expected to be able to meet the needs of students today and in the future. The purpose of this study was to describe the results of student problem solving analysis based on the SOLO Taxonomy. This study used a qualitative descriptive approach to analyze the data. Based on the results of data analysis, it was found that students with different SOLO levels had differences and similarities at each stage of problem solving. At the stage of understanding the problem, the three subjects can identify what is known and what is asked in the problem, only the extended abstract subject adds to make a mathematical model on what is known. At the stage of planning the completion of the three subjects, they were able to mention several concepts, principles and procedures on the problem to solve the problem. At the stage of implementing the plan, the three subjects had already completed the questions based on the plans that had been made, but in the multistructural subject the answers given were not appropriate/relevant to what was asked for in the questions. At the re-examination stage, the three subjects re-examined by re-checking the formula, re-examining the work and recalculation of the results, but only the extended abstract subject could provide several different solutions.